Tissue Resident and Migratory Group 2 Innate Lymphoid Cells - Mathä, Laura; Takei, Fumio; Martinez-Gonzalez, Itziar (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) are present in both mouse and human mucosal and non-mucosal tissues and implicated in initiating type 2 inflammation. ILC2s are considered to be tissue resident cells that develop in the perinatal period and persist throughout life with minimal turning over in adulthood. However, recent studies in animal models have shown their ability to circulate between different organs during inflammation and their potential functions in the destined organs, suggesting their roles in mediating multiple type 2 diseases. Here, we review recent findings on ILC2 migration, including migration within, into and out of tissues during inflammation.